Penggunaan Tepung Jagung pada Pembuatan Muffin dalam Upaya Menciptakan Produk Inovasi dari Tepung Jagung - Valencia Eibel Holdonia; Jasanta Peranginangin; Dewi Hermawati Wahyuningsih (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The rising demand for healthy food is driven by increasing along with public awareness of the importance of a balanced and nutritious diet. One innovation in healthy food products is the development of corn flour-based muffins as an alternative to wheat flour products. Corn flour is a good source contains fiber, B-complex vitamins, and antioxidants such as lutein and zeaxanthin, which are beneficial for health, particularly digestive health and vision. This research aims to formulate healthy corn flour-based muffins with a balanced texture, taste, and nutritional content. The method used includes partially or completely replacing wheat flour with corn flour, as well as adding natural ingredients such as palm sugar as a natural sweetener and vegetable oil as a source of healthy fats. Organoleptic tests were conducted on panelists to assess product acceptability based on appearance, taste, aroma, texture, and color. The results showed that muffins with a composition of 36.5% corn flour and 36.5% wheat flour scored highest in taste and texture, and met the criteria for a healthy food low in sugar and high in fiber. This research demonstrates that corn flour-based muffins are a potential healthy food alternative and can be further developed as part of a healthy lifestyle.